por favor me ajudem na questão 42 eu imploro por favor gente to desesperada
Anexos:
Izzy123:
a) 9
Respostas
respondido por:
1
= - 12 + 4 + 11 - 8 + 13 + 1
= - 12 + 15 - 8 + 14
= 3 + 6
= 9
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
b)
= + 6 + (-14) + (-7) + (+6) + ( + 9)
= 6 - 14 - 7 + 6 + 9
= 6 - 21 + 15
= 15 + 6 - 21
= 21 - 21
= 0
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
c)
= - 2 + 5 + 3 - 2 + 1
= - 2 + 8 - 1
= - 2 + 7
= 5
= - 12 + 15 - 8 + 14
= 3 + 6
= 9
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
b)
= + 6 + (-14) + (-7) + (+6) + ( + 9)
= 6 - 14 - 7 + 6 + 9
= 6 - 21 + 15
= 15 + 6 - 21
= 21 - 21
= 0
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
c)
= - 2 + 5 + 3 - 2 + 1
= - 2 + 8 - 1
= - 2 + 7
= 5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás